INTERPRETATION OF IBN SINA'S WORKS (The Journal of Interdisciplinary Human Studies, 2026)
This article studies and interprets the literary and scientific legacy of Abu Ali ibn Sina (Avicenna), whose works are remarkably comprehensive and many-sided and whose exact number remains unknown. Focusing on his poetic heritage, it examines the manuscript and lithograph copies of his Devon (Diwan) – in particular the copy preserved under inventory no. 15303 in the Center of Oriental Manuscripts in Tashkent and the Iraqi edition of 1957 prepared by Husayn Ali Mahfuz – as well as the collection Awj Zuhal. Special attention is given to his versified medical works (urjuzas), above all the celebrated Urjuza fi al-tibb. The article traces the transmission, translation and publication history of these works across the Islamic world and Europe, including the Latin, Hebrew, Turkish, French, Russian and Uzbek translations and the commentaries of Ibn Rushd and others, and surveys the nine urjuzas attributed to Ibn Sina – eight on medicine and one on logic. It concludes that Ibn Sina rendered complex medical and philosophical ideas in verse with high artistic skill, leaving an inexhaustible spiritual heritage for later generations.
Keywords: Ibn Sina (Avicenna); genre; philosophical views; stanza; commentaries; manuscript; urjuza; medicine; poem; poetry